Update on treatment of adolescent Blount disease. Issue 1 (February 2018) - de Pablos, Julio; Arbeloa-Gutierrez, Lucas; Arenas-Miquelez, Antonio
Abstract : Purpose of review: Treatments available to correct adolescent Blount disease deformities differ in terms of features, advantages, and disadvantages. Each is indicated, therefore, for different scenarios of severity, physeal condition, and maturity. The purpose of this review is to update basic concepts, surgical treatments, and controversies concerning this disorder. Recent findings: The cause of Blount disease is unknown although etiologic factors as morbid obesity and hypovitaminosis D are thought to be associated with it. Recently, semiinvasive techniques (guided growth) have been proposed for mild deformities but remain controversial. Osteotomies with external fixation (hexapodes) are still the most recommended corrective treatment in this condition. Summary: Little is known about the origin and natural history of Blount disease. Treatment is always surgical and, given their complexity, should be preceded by a thorough analysis and planning regarding all deformities. Treatment principles are to correct the three-dimensional deformity and avoid recurrence. The choice of technique mainly depends on patient maturity and severity. Guided growth is a good choice for more immature patients with moderate deformities. Progressive correction using osteotomy or physeal distraction is indicated for patients with severe deformities and low remaining growth. The Taylor spatial frame is currently the most popular progressive correction device.